Pregunta
1. Evaluate the expression for x \( =3, y=4 \), and \( z=5 \). SHOW YOUR WORK. \( z+x(y+z) \)
Ask by George Burgess. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( z + x(y + z) = 32 \)
Solución
Sure, let's evaluate the expression \( z + x(y + z) \) step by step with the given values:
- \( x = 3 \)
- \( y = 4 \)
- \( z = 5 \)
### Step 1: Substitute the Given Values into the Expression
\[
z + x(y + z) = 5 + 3(4 + 5)
\]
### Step 2: Calculate the Value Inside the Parentheses
First, compute \( y + z \):
\[
4 + 5 = 9
\]
Now, the expression becomes:
\[
5 + 3 \times 9
\]
### Step 3: Perform the Multiplication
Multiply \( x \) by the result from Step 2:
\[
3 \times 9 = 27
\]
So, the expression is now:
\[
5 + 27
\]
### Step 4: Add the Remaining Terms
Finally, add \( z \) to the result:
\[
5 + 27 = 32
\]
### Final Answer
\[
z + x(y + z) = 32
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To evaluate the expression \( z + x(y + z) \) for \( x = 3, y = 4, \) and \( z = 5 \), we'll substitute the values in step by step. 1. Substitute the values into the expression: \[ 5 + 3(4 + 5) \] 2. Calculate the sum inside the parentheses: \[ 4 + 5 = 9 \] 3. Now, substitute this back into the expression: \[ 5 + 3 \times 9 \] 4. Calculate the multiplication: \[ 3 \times 9 = 27 \] 5. Finally, add the results together: \[ 5 + 27 = 32 \] So, the final answer is \( 32 \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium